Leydig cell hyperplasia in children: Case series and review. Issue 2 (April 2017) - Mennie, Nicole; King, Sebastian K.; Marulaiah, Mohan; Ferguson, Peter; Heloury, Yves; Kimber, Chris
Summary: Introduction: Leydig cell hyperplasia (LCH) and Leydig cell tumours (LCTs) in children are rare, typically presenting with precocious puberty. Previously, orchidectomy was the routine management; however, more recently, testis-sparing surgery has been performed with good results. We present a series of unusual presentations of LCH, raising new management questions, and a review of the literature regarding LCH and LCT in children. Study design: We performed a literature search using Ovid Medline, PubMed, and Google Scholar, producing 456 articles. We reviewed all case reports and series containing paediatric patients, and relevant review articles. Results: We report three cases of LCH, two of which were incidental findings. All three cases underwent testis-sparing surgery. In the literature there were seven cases of LCH and 101 cases of LCT in prepubertal children. The most common presentation was with precocious puberty. Three cases of LCH and more than two-thirds of LCTs were managed with orchidectomy and overall only 11% of the cases underwent testes-sparing surgery (24% did not specify operative management). There were no reports of recurrence or malignancy. Discussion: Our case series presents three new clinical presentations of LCH that have not previously been reported in the literature: one of incomplete precocious puberty and two with incidental findings on ultrasound in asymptomatic children. Historically, children with the classic presentation of precocious puberty and a testicular lesion have been managed with orchidectomy. Nowadays, many clinicians advocate testes-sparing surgery given there have been no cases of malignancy. In children with no clinical or biochemical signs of precocious puberty, lesions identified on ultrasound can be safely monitored for a period of time. However, if the lesion does not regress, excisional biopsy is recommended to establish the diagnosis, ideally before the onset of puberty. Conclusion: Leydig cell hyperplasia and tumours in pre-pubertal children are benign. Testes-sparing surgery with regular follow-up appears to be safe management.